Revitalization of Local Language in Si Bolang - Rahmayanti, Indah; Hawa, Anni Malihatul; Nofiyanti, Fifi (Tradition and Modernity of Humanity, 2022)
The millennial era and the times have made language change. Not only language but even ethics, manners, and habits change. Indonesians are more interested in films, YouTube, and social media. The existence of Si Bolang shows that highlighting children's activities in the area can be a way to preserve the language. These shows often use regional languages during the dialogue between the character Si Bolang and the local children. In this study, he wanted to know about the revitalization of extinct languages in the 2019 Si Bolang program for language preservation. The research method used is descriptive qualitative. In the research, watching Si Bolang shows in 2019 by selecting 3 shows, then looking for the revitalization of the extinct languages contained in these shows. The results showed that the Si Bolang version shows "Serdadu Kecil Kampung Nelayan Cipanon", "Riang Akur Bocah Selur", and "Penjaga Alam Tanah Jawa". In these shows, language revitalization is becoming extinct or displaced due to the times and the millennial era. The first broadcast used the Sundanese regional language in as much as 40% of all shows due to the dominant language, namely Standard Indonesian. The second and third shows used the Javanese regional language, as much as 60% of all impressions. Because the dialogue used mainly uses the Javanese regional language. The language of instruction or explanation of Si Bolang's activities uses standard Indonesian. This revitalization is essential to be collected and then preserved. The results of this study are helpful for the whole community so that they are more familiar with the diversity of regional languages that are starting to be forgotten or not applied to everyday life. This film contains education and cultural preservation elements, so it needs to be a suggestion for other films to elevate Indonesian culture. With shows or films, it is easier for the audience to understand and more accessible to get the film's meaning. So that it will grow in the community to preserve the existing culture in Indonesia, researchers suggest that various parties can create media to provide impressions that can preserve local languages and introduce culture to the audience.